Guyana. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Guyana during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as financing, training, leadership, exports, marketing, imports, packaging, labeling, beekeeping, waste management and use of fertilizers. Finally, technical assistance was provided for the use of shade houses, the use of biogas, in genetic improvement, pest control and in the value chains of corn, beans and coconut.